Groups with Almost Normal Subgroups of Infinite Rank - Kuchmenko, S. N.; Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study classes of groups whose subgroups of some infinite ranks are almost normal.